2013
DOI: 10.1080/13583883.2013.787450
|View full text |Cite
|
Sign up to set email alerts
|

Commitment in the Context of a Merger

Abstract: Under Title IX, both the Department of Education and private individuals are authorized to bring enforcement actions. In 2011, the U.S. Office of Civil Rights issued a "Dear Colleague" letter, advising higher education institutions on the crafting of an effective response to complaints of sexual harassment. The letter proposed three steps toward the "prompt and equitable" handling of complaints: the creation and dissemination of a nondiscrimination policy, training the parties involved in the investigation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…The development of effective governance cultures (Baird, 2006) The characteristics of effective boards (Rowlands, 2013b) Factors influencing the governance paradigm of universities (Christopher, 2012) The characteristics of higher education leadership (Bryman, 2007) Academics' commitment to mergers (Puusa and Kekäle, 2013) The role of university board members (Kretek, Dragšić and Kehm, 2013) Shared governance (Stensaker and Vabø, 2013) The characteristics of boards (Taylor and de Lourdes Machado, 2008) Tensions between marketization and academization (Ek et al, 2013) The role of university board members (Kretek et al, 2013) Distributed leadership and its effectiveness (van Ameijde et al, 2009) The characteristics of higher education leadership (Bolden, Petrov and Gosling, 2008;Breakwell and Tytherleigh, 2010;Bryman, 2007;Jameson, 2012) Characteristics of supervisory boards (de Boer, Huisman and Meister-Scheytt, 2010) The factors impacting on the functioning of merged institutions (Locke, 2007) Factors influencing the governance paradigm of universities (Christopher, 2012) The characteristics of strategic planning (Lillis and Lynch, 2014) Board members' influence on the boards' identity and work (Meister-Scheytt, 2007;Rytmeister, 2009) External structure and organization…”
Section: Europementioning
confidence: 99%
See 1 more Smart Citation
“…The development of effective governance cultures (Baird, 2006) The characteristics of effective boards (Rowlands, 2013b) Factors influencing the governance paradigm of universities (Christopher, 2012) The characteristics of higher education leadership (Bryman, 2007) Academics' commitment to mergers (Puusa and Kekäle, 2013) The role of university board members (Kretek, Dragšić and Kehm, 2013) Shared governance (Stensaker and Vabø, 2013) The characteristics of boards (Taylor and de Lourdes Machado, 2008) Tensions between marketization and academization (Ek et al, 2013) The role of university board members (Kretek et al, 2013) Distributed leadership and its effectiveness (van Ameijde et al, 2009) The characteristics of higher education leadership (Bolden, Petrov and Gosling, 2008;Breakwell and Tytherleigh, 2010;Bryman, 2007;Jameson, 2012) Characteristics of supervisory boards (de Boer, Huisman and Meister-Scheytt, 2010) The factors impacting on the functioning of merged institutions (Locke, 2007) Factors influencing the governance paradigm of universities (Christopher, 2012) The characteristics of strategic planning (Lillis and Lynch, 2014) Board members' influence on the boards' identity and work (Meister-Scheytt, 2007;Rytmeister, 2009) External structure and organization…”
Section: Europementioning
confidence: 99%
“…Interestingly, these studies focused on the internal organization of universities (Ek et al, 2013;Puusa and Kekäle, 2013;Stensaker and Vabø, 2013), as well as the external organizational relationships among universities (Kyvik and Stensaker, 2013). Ek et al (2013) explored how heads of departments across all faculties of a university deal with the tension between marketization and academization.…”
Section: Europementioning
confidence: 99%
“…Due to the long process, combined with the participatory element, the research process featured many elements traditionally linked to action research (Graumann, 1992;Greenwood & Lewin, 1998). When the identity of an organization is just forming, defense of one's own territory and maintenance of different (structural or imaginary) borders are apparent, but as the process proceeds, the borders become less relevant and the sense of a mutual organization starts to dominate (see Puusa & Kekäle, 2013). According to Billig (1991), this could be seen as a natural part of constructing identity and argumentation.…”
Section: Methods and Datamentioning
confidence: 99%
“…Seen together, Harman and Harman (2003), Kyvik and Stensaker (2013) and Puusa and Kekäle (2013) all point to factors that complicate mergers after the decision to merge is taken. Such findings imply that it is the process after mergers, not the seemingly rational deliberations under external pressure that is crucial for a successful process.…”
Section: Governanced Mergersmentioning
confidence: 99%
“…The argument is that, typically, academics at universities and university colleges have different loyalties and values which represent a particular challenge in crosssectoral mergers. In a recent review of literature on institutional governance structures Frølich and Caspersen (2015) noted the study of Puusa and Kekäle (2013) who investigated a merger process between two Finnish universities. Puusa and Kekäle found that the leadership of the merged university was weaker than the leadership of the two former universities, owing to the lack of time and grounding of the top-down administratively-run merger process.…”
Section: Governanced Mergersmentioning
confidence: 99%